APPROACHES TO DIETOTHERAPY IN HYPERTENSIVE DISEASE - Khasanova, G.Kh.; Tukhtaeva, N.Kh.; Saidov, B.M.; Salikhov, M.U. (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
This article discusses the features of dietotherapy for hypertensive disease, provides recommendations of the World Health Organization, lead European nutritionists and cardiologists.